Relationship between Nurse Knowledge, Attitude, Workloads with Medical Record Completion at the Emergency Unit, Sanglah Hospital, Denpasar - Putri Mastini; Nyoman Tigeh Suryadhi; Alit Suryani (Public Health and Preventive Medicine Archive, 2015)
Backgrounds and purpose: Accuracy and comprehensive maintenance of patient records is an integral part of nursing staff duties. Incomplete documentation could reduce the quality of care and service at the hospital. This study seeks to explore the relationship between nursing staff knowledge, attitude and workloads with accuracy of medical record maintenance at the Emergency Unit in Sanglah Hospital. Methods: Study was cross sectional with a sample of 76 nurses at Emergency Unit Sanglah Hospital. Nurses were interviewed on their knowledge, attitude and workloads. Data on accuracy and completion of medical record was obtained through direct observation. Results: Accuracy and completion of documentation had a significant relationship with knowledge and nurse attitude (p<0,05). Multivariate analysis indicated that nurse knowledge had a significant relationship in completing medical records with adjusted OR=3.7 (95%CI: 1.2- 11.5). This finding indicated that nurses with a higher knowledge on the maintaining medical records was 3.7 times more likely to complete the required documentation compared to nurses with lower knowledge. Conclusion: Accuracy and completion of patient documentation by nurses was significantly associated with their knowledge.